Indonesia's Revitalization of Legal Aid Program : Strengthening Legal Services for the Poor - Zurstrassen, Matthew (World Bank, Washington, DC, 2018)
This briefing note describes several of the main findings of a review of Revitalization of Legal Aid (RLA) conducted in May-June 2007. In particular, it provides a brief background on RLA and posko operations and focuses on activities related to socialization, legal education and case handling. Finally, several lessons learned are outlined. RLA, a pilot project implemented by Justice for the Poor (J4P) Indonesia, has operated since September 2005 in Lampung, West Java, and West Nusa Tenggara (NTB) provinces. RLA seeks to improve access to justice for poor communities through: (a) increasing legal and advocacy skill of paralegals; (b) strengthening the capacity of the existing posko (legal aid posts) to provide legal education, legal aid and mediation services for the community; (c) establishing effective community mediation services through village mediators; and (d) providing recommendations for legal aid policy reform for government at both the national and local levels.